A foamed iron catalyst and a method for its preparation

CN117797841BActive Publication Date: 2026-10-30CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211128647.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2026-10-30
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

但现有技术中对泡沫铁材料比表面积的提升作用有限,且在泡沫铁表面构筑的金属材料结构稳定性差

Benefits of technology

[0021]本发明以泡沫铁为载体,通过一次水热合成反应在泡沫铁表面形成了氧化铁层,进而通过二次水热合成反应在氧化铁层表面引入了金属助剂,还可以再通过气体高温碳化方法在金属助剂附近形成碳化铁层,由此得到了本发明具有多层复合结构Fe@FeOx@M或者Fe@FeOx@FeCx-M的泡沫铁基催化剂。因此,本发明在泡沫铁基底表面构筑了丰富的上述多层结构,由此提供了多活性位,提高了材料的比表面积,进而提高了催化活性。此外,通过形成FeOx+FeCx+助剂M的界面结构,强化了双活性相(FeOx+FeCx)之间以及双活性相和助剂M之间的协同作用,提升了反应性能。同时具有优异的传热、传质性能和高温机械稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003850012650000101
    Figure BDA0003850012650000101
  • Figure BDA0003850012650000111
    Figure BDA0003850012650000111
Patent Text Reader

Abstract

The application discloses a kind of foamed iron catalyst and its preparation method, comprising the following steps: 1) foamed iron is washed pretreatment;2) after foamed iron treated in step 1) with iron salt, lye, hydrothermal additive, deionized water is mixed to carry out first hydrothermal synthesis reaction, after ending, foamed iron is washed and dried;3) after foamed iron treated in step 2) with deionized water, metal salt is mixed, carries out second hydrothermal synthesis reaction, after ending, foamed iron is washed and dried, and the foamed iron catalyst of multilayer composite structure is obtained.The application obtains an iron-based catalyst with high synergy, multiple active sites and strong active metal-assistant interaction, thereby improving the synergy efficiency of reaction and the promotion effect of assistant, improving catalytic performance, while having excellent heat transfer, mass transfer performance and high temperature mechanical stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalytic material preparation technology, specifically to a foamed iron catalyst and its preparation method. Background Technology

[0002] Metal foams are commonly used modular metal-based supports, possessing excellent characteristics such as low-pressure injection pores, three-dimensional fully interconnected mesh structure, high porosity, thermal shock resistance, and compressive strength. Furthermore, the excellent thermal conductivity of metal foam supports makes them superior to ceramic supports, thus attracting considerable attention from researchers. Traditional metal foams include single metal foams such as iron foam, nickel foam, and copper foam, as well as foam alloys such as iron-nickel foam. Wang et al. (B.Wang, J.Sun, M.Abbas, et al., A Novel Hydrothermal Approach for the Synthesis of Flower-Like Fe2O3 / Fe FoamNanoocrystals and Their Superior Performance in Fisher–Tropsch Synthesis. Catalysis Letters, 2017, 147: 1153-1161) prepared Fe2O3 / iron foam-based structured Fischer-Tropsch synthesis catalysts using a hydrothermal synthesis method. During the experiment, the presence of ferric chloride as a reactant caused partial dissolution of the iron foam substrate, resulting in a decrease in mechanical stability. Meanwhile, the surface of the prepared Fe2O3 / foamed iron-based catalyst is hydrophilic, which cannot effectively control water-related side reactions during the catalytic reaction, resulting in excessively high carbon dioxide selectivity in the product selectivity.

[0003] CN111659395B discloses a method for preparing a foamed iron-based catalyst with high all-olefin selectivity, comprising the following steps: S11, removing rust from foamed iron powder using hydrochloric acid, washing with water, and vacuum drying at 55-65℃ for 10-14 hours to obtain solid A; S12, dissolving an oxidizing metal salt in deionized water to obtain solution B; S13, adjusting the pH of solution B with nitric acid to obtain solution C; S14, placing solid A in solution C for chemical surface treatment, filtering after treatment, and drying at 110-130℃ for 10-14 hours to obtain the foamed iron-based catalyst with high all-olefin selectivity. The catalyst prepared by this method uses foamed iron powder as raw material and, through a treatment method centered on chemical surface treatment, prepares a Fischer-Tropsch synthesis catalyst with high all-olefin selectivity, thereby achieving an all-olefin yield ≥60%. However, the existing technology has limited effect on increasing the specific surface area of ​​foamed iron materials, and the metal material structure constructed on the surface of foamed iron has poor stability. Summary of the Invention

[0004] In view of this, the main objective of the present invention is to provide a foamed iron catalyst and its preparation method, which yields an iron-based catalyst with highly synergistic multiple active sites and strong active metal Fe-promoter interaction, exhibiting good catalytic activity, as well as excellent heat transfer, mass transfer performance and high-temperature mechanical stability.

[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: a method for preparing a foamed iron catalyst, comprising the following steps:

[0006] 1) Clean and pre-treat the foamed iron;

[0007] 2) Mix the foamed iron treated in step 1) with iron salt, alkali solution, hydrothermal additive and water and carry out a hydrothermal synthesis reaction. After the reaction is completed, wash and dry.

[0008] 3) The foamed iron treated in step 2) is mixed with water and metal salt to carry out a secondary hydrothermal synthesis reaction. After the reaction is completed, it is washed and dried to obtain a multilayer composite structure foamed iron catalyst.

[0009] According to the preparation method of the present invention, in step 1), the pre-treatment of cleaning includes: ultrasonically treating the foamed iron successively in hydrochloric acid solution, anhydrous ethanol solution, and deionized water, followed by drying. In a specific embodiment, the foamed iron can be first ultrasonically cleaned in hydrochloric acid solution to remove surface oxide layers and other impurities, then ultrasonically cleaned in anhydrous ethanol solution to remove surface oily substances, and finally ultrasonically cleaned with deionized water and then dried. In another specific embodiment, the foamed iron can also be first ultrasonically cleaned in anhydrous ethanol solution to remove surface oily substances, then ultrasonically cleaned in hydrochloric acid solution to remove surface oxide layers, and finally ultrasonically cleaned with deionized water and then dried. Preferably, the concentration of hydrochloric acid solution can be selected as 0.05-0.3M, the ultrasonic cleaning time of hydrochloric acid solution, anhydrous ethanol solution, or deionized water is 3-8 min, the final drying temperature of the foamed iron is 60-150℃, and the drying time is 2-4 h.

[0010] According to the preparation method of the present invention, the pore size of the foamed iron ranges from 0.5 to 20 μm, and the specific surface area ranges from 1 to 50 m². 2 / g.

[0011] According to the preparation method of the present invention, in step 2), the temperature of the primary hydrothermal synthesis reaction is 100-140℃, the reaction time is 8-12h, and the drying temperature is 60-150℃, the drying time is 10-14h. Through the primary hydrothermal synthesis reaction, an iron oxide layer is formed on the surface of the foamed iron.

[0012] According to the preparation method of the present invention, in step 2), the mass ratio of foamed iron: iron salt: alkaline solution: hydrothermal additive: water is (2-8):(1-5):(0.5-2):(0.1-1):60.

[0013] According to the preparation method of the present invention, in step 2), the iron salt is selected from one or more of ferric nitrate, ferric chloride, ferric sulfate, ferric ammonium citrate, or ferric oxalate; the alkaline solution is selected from one or more of urea, ammonia, sodium hydroxide, or potassium hydroxide to promote the hydrolysis of the precursor salt. The hydrothermal additive can be selected as NH4F to adjust the distribution of metal ions during the hydrothermal synthesis process.

[0014] According to the preparation method of the present invention, in step 3), the metal salt is selected from one or more of potassium permanganate, sodium permanganate, magnesium permanganate, trisodium citrate, manganese nitrate, zinc nitrate, cobalt nitrate, copper nitrate, copper sulfate, ferric sulfate, and zirconium oxynitrate. The mass ratio between the metal salt and the foamed iron raw material in step 2) is (0.3-2):3, preferably (0.3-1.5):3.

[0015] According to the preparation method of the present invention, in step 3), the temperature of the secondary hydrothermal synthesis reaction is 120-160℃, the reaction time is 20-28h, and the drying temperature is 70-150℃, the drying time is 10-14h. Through the secondary hydrothermal synthesis reaction, a metal additive M is introduced onto the surface of the foamed iron oxide layer, where M is one or more of Mn / Na / Zn / Mg / Co / Cu / K / S / Zr.

[0016] According to the preparation method of the present invention, preferably, in step 3), glucose or tetraethyl orthosilicate may be added simultaneously with the addition of the metal salt. This introduces C or Si elements along with the metal auxiliary M, thereby controlling the type and electronic structure of the surface iron phase and further increasing the specific surface area of ​​the catalyst.

[0017] According to the preparation method of the present invention, step 4) is further included: the foamed iron catalyst treated in step 3) is subjected to high-temperature carbonization treatment at 250-450°C in the presence of one or more gases, namely syngas, CO or H2, and an iron carbide layer is formed on the surface of the iron oxide layer of the foamed iron.

[0018] In another aspect, the present invention provides a foamed iron catalyst prepared by the above method, wherein the multilayer composite structure is Fe@FeOx@FeCx-M or Fe@FeOx@M, where M is one or more of Mn / Na / Zn / Mg / Co / Cu / K / S / Zr, and M exists in the form of an element or an oxide.

[0019] In another aspect, the present invention provides the application of the foamed iron catalyst prepared by the above method for use in CO2 hydrogenation reaction, Fischer-Tropsch synthesis reaction or CO methanation reaction.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] This invention uses foamed iron as a carrier. An iron oxide layer is formed on the surface of the foamed iron through a primary hydrothermal synthesis reaction. A metal additive is then introduced onto the surface of the iron oxide layer through a secondary hydrothermal synthesis reaction. Furthermore, an iron carbide layer can be formed near the metal additive through a high-temperature gas carbonization method. This yields a foamed iron-based catalyst with a multilayered composite structure of Fe@FeOx@M or Fe@FeOx@FeCx-M. Therefore, this invention constructs abundant multilayered structures on the surface of the foamed iron substrate, providing multiple active sites, increasing the specific surface area of ​​the material, and thus improving catalytic activity. In addition, by forming an interface structure of FeOx+FeCx+additive M, the synergistic effect between the two active phases (FeOx+FeCx) and between the two active phases and the additive M is enhanced, improving reaction performance. It also exhibits excellent heat transfer, mass transfer performance, and high-temperature mechanical stability. Detailed Implementation

[0022] The present invention will be further described below with reference to the embodiments. However, the present invention is not limited to the listed embodiments, but should also include equivalent improvements and modifications of the technical solutions defined in the appended claims of the present invention.

[0023] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0024] In the following examples and comparative examples:

[0025] (1) Main raw materials

[0026] The raw material for the foamed iron was obtained from commercially available sources, and its specific surface area was measured to be 14.8 m². 2 / g.

[0027] Unless otherwise specified, all raw materials used in this invention are commercially available and are analytical grade reagents.

[0028] (2) Characterization and Testing

[0029] Conversion rate and selective acquisition process:

[0030] The reaction products were analyzed online and offline using a gas chromatograph (GC-2014C, Shimadzu, Japan) with a flame ionization detector (FID). A Porapak-Q column was used for online separation of C1 to C5 hydrocarbons, while an SE-30 column was used for offline separation of C6 to C20 hydrocarbons. H2, CO, CH4, and CO2 in the reaction products were analyzed online using a thermal conductivity detector (TCD) with an activated carbon column as the stationary phase. The selectivity of various alkenes and alkanes was calculated using the external standard method based on the FID results. The carbon balance of all reactions was calculated to be above 95%.

[0031] The specific surface area was determined using a nitrogen physical adsorption method. The instrument used was a Micromeritics ASAP 2020 (Micromeritics, USA).

[0032] The following examples are all used to illustrate the foamed iron catalyst and its preparation method of the present invention.

[0033] Example 1

[0034] 1) Weigh 3.0g of foamed iron into a beaker, add 30mL of 0.1M HCl, treat for 3min and then remove the foamed iron; add 30mL of anhydrous ethanol, sonicate for 5min and then remove; add 30mL of deionized water, sonicate for 5min and then remove, then rinse with deionized water 3 times; finally put it into an 80℃ oven to dry for 3h.

[0035] 2) Weigh 0.82g Fe(NO3)3·9H2O (2mmol), 0.606g urea (10mmol), and 3.0g of foamed iron into a hydrothermal synthesis reactor, add 0.308g NH4F (8mmol), then add 36mL of deionized water, mix thoroughly, seal, and place in a 120℃ rotary oven for 10h. Take out the sample after the reaction is complete, wash it several times with deionized water, and place the foamed iron in a 60℃ vacuum oven for 12h to dry.

[0036] 3) Add all the sample obtained in 2) to a hydrothermal reactor, add 1.0 g of KMnO4 solid, add 36 mL of deionized water, mix thoroughly, seal, and place in a rotary oven at 140℃ for 24 h, then allow to cool naturally to room temperature. Remove the sample, wash with deionized water, and dry in a vacuum oven at 80℃ for 12 h to obtain the foamed iron catalyst. The specific surface area was measured to be 45.6 m². 2 / g.

[0037] Example 2

[0038] 1) Weigh 2.0g of foamed iron into a beaker, add 30mL of 0.05M HCl, treat for 3min and then remove the foamed iron; add 30mL of anhydrous ethanol, sonicate for 5min and then remove; add 30mL of deionized water, sonicate for 5min and then remove, then rinse with deionized water 3 times; finally put it in an 80℃ oven to dry for 3h.

[0039] 2) Weigh 0.6g Fe(NO3)3·9H2O, 0.3g urea, and 1.2g of foamed iron into a hydrothermal synthesis reactor, add 0.06g NH4F, then add 36mL of deionized water, mix thoroughly, seal, and place in a 120℃ rotary oven for 10h. Take out the sample after the reaction is complete, wash it several times with deionized water, and place the foamed iron in a 60℃ vacuum oven to dry for 12h.

[0040] 3) Add all the sample obtained in 2) to a hydrothermal reactor, add 0.4 g of KMnO4 solid, add 36 mL of deionized water, mix thoroughly, seal, and place in a 140℃ rotary oven for 24 h. Allow it to cool naturally to room temperature. Remove the sample, wash with deionized water, and dry in an 80℃ vacuum oven for 12 h to obtain the foamed iron catalyst. The specific surface area was measured to be 43.2 m². 2 / g.

[0041] Example 3

[0042] 1) Weigh 5.0g of foamed iron into a beaker, add 30mL of 0.3M HCl, treat for 3min and then remove the foamed iron; add 30mL of anhydrous ethanol, sonicate for 5min and then remove; add 30mL of deionized water, sonicate for 5min and then remove, then rinse with deionized water 3 times; finally put it into an 80℃ oven to dry for 3h.

[0043] 2) Weigh 3.0g Fe(NO3)3·9H2O, 1.2g urea, and 4.8g of foamed iron into a hydrothermal synthesis reactor, add 0.6g NH4F, then add 36mL of deionized water, mix thoroughly, seal, and place in a 120℃ rotary oven for 10h. Take out the sample after the reaction is complete, wash it several times with deionized water, and place the foamed iron in a 60℃ vacuum oven to dry for 12h.

[0044] 3) Add all the sample obtained in 2) to a hydrothermal reactor, add 0.4 g of KMnO4 solid, add 36 mL of deionized water, mix thoroughly, seal, and place in a 140℃ rotary oven for 24 h. Allow it to cool naturally to room temperature. Remove the sample, wash with deionized water, and dry in an 80℃ vacuum oven for 12 h to obtain the foamed iron catalyst. The specific surface area was measured to be 41.8 m². 2 / g.

[0045] Example 4

[0046] Based on Example 1, KMnO4 in step 3) was replaced with magnesium permanganate at an addition amount of 0.3g, resulting in a foamed iron catalyst with a specific surface area of ​​51.5m². 2 / g.

[0047] Example 5

[0048] Based on Example 1, KMnO4 in step 3) was replaced with manganese nitrate at a dosage of 1.5 g, resulting in a foamed iron catalyst with a specific surface area of ​​44.7 m². 2 / g.

[0049] Example 6

[0050] Based on Example 1, in step 3), KMnO4 was replaced with 1.0g of solid KMnO4 and 1.0g of solid glucose to introduce auxiliary agents C and K, resulting in a foamed iron catalyst with a specific surface area of ​​53.2m². 2 / g.

[0051] Example 7

[0052] Based on Example 1, KMnO4 in step 3) was replaced with copper sulfate to introduce the additives S and Cu, resulting in a foamed iron catalyst with a specific surface area of ​​48.4 m². 2 / g.

[0053] Example 8

[0054] Based on Example 1, in step 3), KMnO4 was replaced with 1.0g of solid KMnO4 and 1.0g of TEOS (tetraethyl orthosilicate) to introduce the additives Si and K, resulting in a foamed iron catalyst with a specific surface area of ​​63.9m². 2 / g.

[0055] Example 9

[0056] Based on Example 1, the temperature of the primary hydrothermal synthesis reaction in step 2) was changed to 100°C and the reaction time to 12 hours, while the drying temperature was changed to 60°C and the drying time to 14 hours. The temperature of the secondary hydrothermal synthesis reaction in step 3) was changed to 120°C and the reaction time to 28 hours, while the drying temperature was changed to 70°C and the drying time to 14 hours. The resulting foamed iron catalyst had a specific surface area of ​​41.3 m². 2 / g.

[0057] Example 10

[0058] Based on Example 1, the temperature of the primary hydrothermal synthesis reaction in step 2) was changed to 140°C and the reaction time to 8 hours, while the drying temperature was changed to 150°C and the drying time to 10 hours. The temperature of the secondary hydrothermal synthesis reaction in step 3) was changed to 160°C and the reaction time to 20 hours, while the drying temperature was changed to 150°C and the drying time to 10 hours. The resulting foamed iron catalyst had a specific surface area of ​​38.4 m². 2 / g.

[0059] Example 11

[0060] The foamed iron catalyst treated in step 3) of Example 1 was subjected to reduction carbonization treatment at 250°C by passing H2 through it to obtain the product, which had a specific surface area of ​​53.1 m². 2 / g.

[0061] Example 12

[0062] The foamed iron catalyst treated in step 3) of Example 1 was passed through syngas (H2 / CO volume ratio of 1) and subjected to high-temperature carbonization at 450°C to obtain the product, which had a measured specific surface area of ​​49.5 m². 2 / g.

[0063] Comparative Example 1

[0064] Weigh 3.0g of foamed iron into a beaker, add 30mL of 0.1M HCl, treat for 3min and then remove the foamed iron; add 30mL of anhydrous ethanol, sonicate for 5min and then remove; add 30mL of deionized water, sonicate for 5min and then remove, then rinse 3 times with deionized water; finally put it into an 80℃ oven to dry for 3h.

[0065] 0.82 g of Fe(NO3)3·9H2O (2 mmol), 0.606 g of urea (10 mmol), and 3.0 g of iron foam were weighed into a hydrothermal synthesis reactor. 0.308 g of NH4F (8 mmol) was added, followed by 36 mL of deionized water. The mixture was thoroughly mixed, sealed, and placed in a rotary oven at 120 °C for 10 h. The reacted sample was then removed, washed several times with deionized water, and the iron foam was dried in a vacuum oven at 60 °C for 12 h to obtain the catalyst. The specific surface area was determined to be 38.1 m². 2 / g.

[0066] Comparative Example 2

[0067] 8.0 g of foamed iron was weighed into a 250 mL beaker, treated with 60 mL of 1 M hydrochloric acid for 25 min, the hydrochloric acid was poured out, and the sample was washed three times with 60 mL of deionized water. Then, 60 mL of anhydrous ethanol was added, and the sample was ultrasonically cleaned for 15 min. The ethanol was poured out, and the sample was washed three times with 60 mL of deionized water. Then, 60 mL of deionized water was added, and the sample was ultrasonically cleaned for 15 min. The deionized water was poured out, and the foamed iron was rinsed with 1 L of deionized water. The treated foamed iron was then placed in a vacuum oven, evacuated to -0.1 MPa, dried at 60 °C for 8 h, and allowed to cool naturally to room temperature. The sample was then removed. Finally, 5.0 g of the acid-washed foamed iron was weighed into a ceramic boat, spread evenly on the surface, and placed in a muffle furnace. The temperature was increased to 340 °C at a rate of 3 °C / min, held for 5 h, and allowed to cool naturally to room temperature. The catalyst was then obtained. The specific surface area was measured to be 10.9 m². 2 / g.

[0068] Comparative Example 3

[0069] First, 8.0 g of calcined iron foam was weighed into a ceramic boat and evenly spread on the surface. The boat was then placed in a muffle furnace and heated to 340 °C at a rate of 3 °C / min, and held at that temperature for 5 hours. After natural cooling to room temperature, the foam was removed. Next, 6.0 g of calcined iron foam was weighed into a 250 mL beaker and treated with 60 mL of 1 M hydrochloric acid for 25 minutes. The hydrochloric acid was then poured off, and the foam was washed three times with 60 mL of deionized water. Then, 60 mL of anhydrous ethanol was added, and the foam was ultrasonically cleaned for 15 minutes. The ethanol was then poured off, and the foam was washed three times with 60 mL of deionized water. Finally, 60 mL of deionized water was added, and the foam was ultrasonically cleaned for 15 minutes. The deionized water was then poured off, and the foam was rinsed with 1 L of deionized water. Finally, the treated iron foam was placed in a vacuum oven, evacuated to -0.1 MPa, and dried at 60 °C for 8 hours. After natural cooling to room temperature, the sample was removed, yielding the catalyst. The specific surface area was measured to be 12.5 m². 2 / g.

[0070] Comparative Example 4

[0071] Weigh 3.0g of foamed iron into a 50mL beaker, add 30mL of 0.1M HCl and treat for 3min; add 30mL of anhydrous ethanol and ultrasonically clean for 5min; add 30mL of deionized water and ultrasonically clean for 5min, then rinse several times with plenty of deionized water; finally, place it in an 80℃ oven to dry for 3h.

[0072] Weigh 0.82 g Fe(NO3)3·9H2O (2 mmol), 0.606 g urea (10 mmol), and 3.0 g of foamed iron into a hydrothermal reactor. Add 0.308 g NH4F (8 mmol), then add 36 mL of deionized water, mix thoroughly, seal, and place in a 120°C rotary oven for 10 h. Remove the reacted sample, wash several times with deionized water, and dry in a 60°C vacuum oven for 12 h. Finally, calcine the sample in a 350°C muffle furnace for 3 h. After cooling to room temperature, remove the sample to obtain the catalyst. The specific surface area was measured to be 28.6 m². 2 / g.

[0073] Comparative Example 5

[0074] Weigh 3.0g of foamed iron into a 50mL beaker, add 30mL of 0.1M HCl and treat for 3min; add 30mL of anhydrous ethanol and ultrasonically clean for 5min; add 30mL of deionized water and ultrasonically clean for 5min, then rinse several times with plenty of deionized water; finally, place it in an 80℃ oven to dry for 3h.

[0075] Weigh 0.82g Fe(NO3)3·9H2O (2mmol), 0.606g urea (10mmol), and 3.0g of foamed iron into a hydrothermal reactor, add 0.308g NH4F (8mmol), then add 36mL of deionized water, mix thoroughly, seal, and place in a 120℃ rotary oven for 10h. Take out the reacted sample, wash it several times with deionized water, place it in a 60℃ vacuum oven for 12h, and finally place the sample in a 350℃ muffle furnace for 3h. Take it out when the temperature drops to room temperature.

[0076] All the above samples were added to a hydrothermal reactor, along with 0.2 g of KMnO4 solid and 36 mL of deionized water. The mixture was thoroughly mixed, sealed, and placed in a rotary oven at 140°C for 24 hours. The mixture was then allowed to cool naturally to room temperature. The sample was removed, washed several times with deionized water, and dried in a vacuum oven at 80°C for 12 hours to obtain the catalyst. The specific surface area was measured to be 27.2 m². 2 / g.

[0077] The catalysts prepared according to the embodiments and comparative examples of the present invention were subjected to application tests to test their catalytic performance. The specific application steps are as follows:

[0078] 1 g of catalyst was reduced in a fixed bed with syngas (volume ratio H2 / CO = 1) under the following conditions: 350 °C, 0.1 MPa, for 5000 h. -1(V / V), constant temperature for 10 h; after reduction, the reduced catalyst was cooled to room temperature in a nitrogen stream, and then the nitrogen was switched to the reaction gas (volume ratio H2 / CO2 = 3) to start the CO2 hydrogenation reaction; the reaction conditions were 300℃, 0.5MPa, 2500 h. -1 (V / V), the reaction results are shown in Table 1 below.

[0079] Table 1

[0080]

[0081]

[0082] As can be seen from the data in Table 1 above, the embodiments of the present invention obtained foamed iron catalysts with Fe@FeOx@M (as in Example 1) or Fe@FeOx@FeCx-M (as in Examples 11-12) composite structures through two-step hydrothermal synthesis. A rich hierarchical structure was constructed on the surface of the foamed iron substrate, increasing the specific surface area of ​​the material and thus improving the catalytic activity and CO2 conversion rate. Furthermore, by forming an interfacial structure of FeOx+FeCx+promoter M, the synergistic effect between the two active phases (FeOx+FeCx) and between the two active phases and the promoter was strengthened, improving the reaction performance. The substrate material used in the embodiments of the present invention is foamed iron (elemental iron metal), which therefore has excellent thermal transfer and mechanical stability. In addition, the foamed iron material has an open macroporous structure, which is beneficial for enhancing the mass transfer performance of reactants and products on the foamed iron catalyst.

[0083] The preparation methods in Comparative Examples 1-5, however, fail to construct a rich multilayer structure, resulting in a low specific surface area of ​​the material, leading to poor catalytic performance, low CO2 conversion rate, and excessively high selectivity for the byproduct CH4. Therefore, by setting up a multi-step hydrothermal synthesis process and coordinating it with the calcination process according to the embodiments of this invention, a rich multilayer structure can be effectively constructed on the surface of the foamed iron substrate. Furthermore, the phase composition and proportion of the multilayer structure can be controlled according to requirements, thereby improving catalytic reaction performance and obtaining a highly active and selective iron-based catalyst.

[0084] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all embodiments here. All obvious variations or modifications derived from the technical solutions of the present invention are within the spirit and scope of the present invention.

Claims

1. A method for preparing a foamed iron catalyst, characterized in that: Includes the following steps: 1) Clean and pre-treat the foamed iron; 2) Mix the foamed iron treated in step 1) with iron salt, alkaline solution, hydrothermal additive NH4F and water to carry out a hydrothermal synthesis reaction. After the reaction, wash the foamed iron and dry it. 3) The foamed iron treated in step 2) is mixed with water and metal salt to carry out a secondary hydrothermal synthesis reaction. After the reaction, the foamed iron is washed and dried to obtain a multilayer composite foamed iron catalyst. The metal salt is selected from one or more of potassium permanganate, sodium permanganate, magnesium permanganate, manganese nitrate, zinc nitrate, cobalt nitrate, copper nitrate, and copper sulfate. An iron oxide layer was formed on the surface of the foamed iron through a first hydrothermal synthesis reaction, and then a metal additive was introduced on the surface of the iron oxide layer through a second hydrothermal synthesis reaction. In step 2), the temperature of the first hydrothermal synthesis reaction is 100-140℃, the reaction time is 8-12h, the drying temperature is 60-150℃, and the drying time is 10-14h. In step 2), the mass ratio of foamed iron: iron salt: alkaline solution: hydrothermal additive: water is (2-8):(1-5):(0.5-2):(0.1-1):60; In step 3), the mass ratio between the metal salt and the foamed iron in step 2) is 0.1-0.5:1; In step 3), the temperature of the secondary hydrothermal synthesis reaction is 120-160℃, the reaction time is 20-28h, the drying temperature is 70-150℃, and the drying time is 10-14h.

2. The method for preparing the foamed iron catalyst according to claim 1, characterized in that: In step 1), the cleaning pretreatment includes: placing the foamed iron in hydrochloric acid solution, anhydrous ethanol solution and deionized water in sequence for ultrasonic treatment and drying; wherein, the concentration of hydrochloric acid solution is 0.05-0.3M, the ultrasonic cleaning time of hydrochloric acid solution, anhydrous ethanol solution or deionized water is 3-8min, the drying temperature of foamed iron is 60-150℃, and the drying time is 2-4h.

3. The method for preparing the foamed iron catalyst according to claim 1, characterized in that: The foamed iron has a pore size ranging from 0.5 to 20 μm and a specific surface area ranging from 1 to 50 m². 2 / g.

4. The method for preparing the foamed iron catalyst according to any one of claims 1-3, characterized in that: It also includes step 4): the foamed iron catalyst treated in step 3) is subjected to high-temperature carbonization treatment at 250-450°C in the presence of syngas or CO.

5. A foamed iron catalyst prepared by the method according to any one of claims 1-3, wherein it has a multilayer composite structure: Fe@FeOx@M, wherein, M is one or more of Mn / Zn / Co / Cu, and M exists in oxide form.

6. The foamed iron catalyst prepared by the method of claim 4, having a multilayer composite structure: Fe@FeOx@FeCx-M, wherein, M is one or more of Mn / Zn / Co / Cu, and M exists in the form of an element or an oxide.

7. The application of the foamed iron catalyst prepared by the method of any one of claims 1-4, for use in CO2 hydrogenation reaction, Fischer-Tropsch synthesis reaction or CO methanation reaction.

Citation Information

Patent Citations

  • Preparation method of array-shaped multi-stage-structured cobalt nickel sulfide / foamed nickel supercapacitor electrode

    CN107492452A